Smart Local Backup Protection for Smart Substation - M.N. Dazahra; F. Elmariami; A. Belfqih; J. Boukherouaa (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents a novel smart local backup protection SLBP used for the support and backup of the protective relays in a smart substation. The proposed SLBP is based on the IEC61850 standards and the concept consists of the acquisition of Generic Object Oriented Substation Event GOOSE used for tripping and interlocks exchange between Intelligent Equipment Devices IEDs and the reading of the Sampled Value SV existing in the process bus coming from Mergin Units MU or Non-Conventional Instrument Transformers NCIT. Several logical schemes to protect different zones of the substation are presented and how can be integrated using data in the substation automation system. The SLBP was developed using an open source library and free operating system. Moreover, a low cost prototype is presented in order to evaluate the efficiency and the operation of the SLBP under diverse scenarios of the proposed logical protective schemes such us breaker failure and overcurrent protection